Monoamine Release in the Cat Lumbar Spinal Cord during Fictive Locomotion Evoked by the Mesencephalic Locomotor Region - Noga, Brian R.; Turkson, Riza P.; Xie, Songtao; Taberner, Annette; Pinzon, Alberto; Hentall, Ian D. (Frontiers in Neural Circuits, 2017)
Spinal cord neurons active during locomotion are innervated by descending axons that release the monoamines serotonin (5-HT) and norepinephrine (NE) and these neurons express monoaminergic receptor subtypes implicated in the control of locomotion. The timing, level and spinal locations of release of these two substances during centrally-generated locomotor activity should therefore be critical to this control. These variables were measured in real time by fast-cyclic voltammetry in the decerebrate cat’s lumbar spinal cord during fictive locomotion, which was evoked by electrical stimulation of the mesencephalic locomotor region (MLR) and registered as integrated activity in bilateral peripheral nerves to hindlimb muscles. Monoamine release was observed in dorsal horn (DH), intermediate zone/ventral horn (IZ/VH) and adjacent white matter (WM) during evoked locomotion. Extracellular peak levels (all sites) increased above baseline by 138 ± 232.5 nM and 35.6 ± 94.4 nM (mean ± SD) for NE and 5-HT, respectively. For both substances, release usually began prior to the onset of locomotion typically earliest in the IZ/VH and peaks were positively correlated with net activity in peripheral nerves. Monoamine levels gradually returned to baseline levels or below at the end of stimulation in most trials. Monoamine oxidase and uptake inhibitors increased the release magnitude, time-to-peak (TTP) and decline-to-baseline. These results demonstrate that spinal monoamine release is modulated on a timescale of seconds, in tandem with centrally-generated locomotion and indicate that MLR-evoked locomotor activity involves concurrent activation of descending monoaminergic and reticulospinal pathways. These gradual changes in space and time of monoamine concentrations high enough to strongly activate various receptors subtypes on locomotor activated neurons further suggest that during MLR-evoked locomotion, monoamine action is, in part, mediated by extrasynaptic neurotransmission in the spinal cord.